Does digitalization drive corporate green transformation?—Based on evidence from Chinese listed companies - Peng, Cheng; Jia, Xinyuan; Zou, Yu (Frontiers in Environmental Science, 2022)
Accelerating the digital transformation of enterprises, digital depth to empower business operations and management, and drive green transformation, is an essential task to further promote the digital construction of a country. This paper explores the impact of digitalization on the green transformation of enterprises and its inner mechanism based on the text data mining method, using A-share listed companies in Shanghai and Shenzhen from 2011 to 2020 as research samples. The results show that digitalization has the effect of "inhibiting" and then "enhancing" the green transformation of enterprises, i.e., the relationship between the two is "U" shaped. The heterogeneity analysis shows that this "U"-shaped relationship exists among non-heavy polluting enterprises, eastern enterprises, mainboard enterprises, GEM enterprises, and enterprises with high digitization speed. In the path of action, the dynamic capability acts as a partial mediator in the relationship between digitalization and green transformation. This study provides a useful reference for enterprises to use digitalization as a grip to drive sustainable development and promote the construction of a national ecological civilization.